A Phase I Study of FOLFIRINOX Plus IPI-926, a Hedgehog Pathway Inhibitor, for Advanced Pancreatic Adenocarcinoma. Issue 3 (March 2016) - Ko, Andrew H.; LoConte, Noelle; Tempero, Margaret A.; Walker, Evan J.; Kate Kelley, R.; Lewis, Stephanie; Chang, Wei-Chou; Kantoff, Emily; Vannier, Michael W.; Catenacci, Daniel V.; Venook, Alan P.; Kindler, Hedy L.
Abstract : Objectives: In mouse models of pancreatic cancer, IPI-926, an oral Hedgehog inhibitor, increases chemotherapy delivery by depleting tumor-associated stroma. This multicenter phase Ib study evaluated IPI-926 in combination with FOLFIRINOX (5-fluorouracil, leucovorin, irinotecan, oxaliplatin) in patients with advanced pancreatic cancer. Methods: Patients were treated with once-daily IPI-926 plus FOLFIRINOX. A 3 + 3 dose escalation design was used, with cohort expansion at the maximum tolerated dose. A subset of patients underwent perfusion computed tomography to assess changes in tumor perfusion. Results: The maximum tolerated dose was identified 1 dose level below standard FOLFIRINOX. Common treatment-related adverse events included liver function test abnormalities, neuropathy, nausea/vomiting, and diarrhea. Objective response rate was high (67%), and patients receiving IPI-926 maintenance showed further declines in CA19-9 levels even after FOLFIRINOX discontinuation. Treatment did not result in consistent increases in tumor perfusion. The study closed early when a separate phase II trial of IPI-926 plus gemcitabine indicated detrimental effects of this combination. Conclusions: This is the first study to demonstrate the feasibility of using FOLFIRINOX as the chemotherapeutic backbone in a clinical trial design. Although robust antitumor activity and acceptable safety were observed with the addition of IPI-926 to this regimen, future development of Hedgehog inhibitors in pancreatic cancer seems unlikely. Abstract : Supplemental digital content is available in the text.